Self-perception and performance of queer identity by young LGBTQ+ people in Ha Noi = Sự tự nhận định và biểu hiện danh tính Queer bởi giới trẻ thuộc nhóm LGBTQ+ tại Hà Nội - Nguyễn, Thanh Phương (2021)
This qualitative research project studies the way in which the Vietnamese queer youth (including lesbian, gay, bisexual, transgender, queer, and genderqueer) conceptualize their identities, and the interplay between their self-conceptualization, gender performance, and their interpretation of roles in relationships. The collected data involves qualitative interviews conducted on nine young queer people in Vietnam. This research also includes the author’s observations and notes on the interactions with the informants in interview settings and on their social media profiles. Data from semistructured interviews suggests that many informants only loosely follow the model of homonormativity, gender norms, and an essentialist characterization of queerness, while a constructivist viewpoint was also in place for those who get more exposure to Western literature. The findings also reveal the emergence of a queer subgroup that does not conform to the homonormativity shown in the majority of LGBTQ+ discourse in Vietnam. The findings suggest that there exists a dissonance between queer representation in the media and the real picture of their various identities. Guided by feminist methodology, this qualitative study aims to explore marginalized identities and question the dominant gendered structures that grant social acceptance to some queer identities while further marginalizing other queers through the regulation of gender performance. Further analysis is suggested to yield results of a higher level of significance for the study.